Women's Empowerment amid the Challenges and Opportunities of Gender Equality in The Digital Era from an Islamic Perspective - Rahmat Hidayat; M. Yoga Jusri Pratama; Naurah Athaya; Alya Syafitri Lubis; Achmad Rofiqo Ridho (Social Science Academic, 2026)
This research is motivated by the persistently low representation of women in organizational leadership due to traditional gender bias and digital literacy challenges. The main objective of the activity is to deconstruct the understanding of women's social roles and improve the practical organizational skills of female cadres. The method applied is participatory action research (PAR) through the implementation of educational interventions, focus group discussions, and tactical simulations based on behavioral modeling (Neuro-Linguistic Programming/NLP). The main activity focuses on reconstructing the understanding of the natural values of humanity in inclusive Islam and honing digital communication skills. The impact of this activity has proven significant in increasing critical awareness, restoring self-confidence, and breaking down the internal psychological barriers (inner glass ceiling) of cadres to take on strategic roles in the public sphere. The research conclusion shows that the integration of inclusive theological understanding with tactical digital skills training is a highly effective and precise social engineering instrument in addressing the root causes of gender inequality.